Preparation and Characterization Nanoparticle Calcium Oxide from Snakehead Fish Bone using Ball Milling Method - Muryati Muryati; Poedji Loekitowati Hariani; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Snakehead Fish Bone (SFB) is a waste from food processing in Palembang. Fish bones have calcium content so they have a potential as a source of Calcium Oxide (CaO). Calcination of fish bones was carried out at a temperature of 900oC with variations of time 1, 2, 3, and 4 hours. The Nanoparticle Calcium Oxide (NCO) was prepared using the ball milling method. This study aims to make NCO as a raw material for hydroxyapatite synthesis. The NCO was characterized using Fourier Transform Infra-Red (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microscope (SEM). Characterization using FTIR shows that NCO has functional groups O-H, CO32- and PO43- functional groups. XRD analysis shows that NCO has an average particle size of 38.9445 nm.Analysis using SEM shows particles in the form of granules of almost uniform size. The NCO produced eligible of the nanomaterial and has the potential as a raw material for synthesis of hydroxyapatite.Keywords: Nanomaterial, ball milling, calcium oxide, fish bone